In Search of a Unity or Persistence of Tragedy? On Simmel’s City Writings - Mele, Vincenzo (Simmel Studies)

(untitled) (Edizioni ETS, 2023)
This article is devoted to an analysis of Simmel’s “metaphysical longing” (metaphysische Sehnsucht) and its consequences for his cultural and sociological analysis of the city and, consequently, modernity. Simmel’s “metaphysical longing” expresses itself equally in the sought-after relationship between part and whole, surface and depth, reality and idea. It intends to explore especially how this approach is developed in Simmel’s so-called minor essays, including the essays on historic Italian cities that are often referred to as those most characteristic of this metaphysical longing for unity. However, to understand the essence and characteristics of this approach, it is necessary to explore other minor, preparatory essays, coeval with and following the Philosophy of Money, which attest to Simmel’s path toward the construction of what he himself had defined as “sociological aesthetics,” that is, a space of analysis intermediate between philosophy and empirical sociological science. At the end of this path, we will see some stages of Simmel’s conceptual journey from nostalgia as Sehnsucht toward acceptance of the tragedy of culture, that is, the impossibility for man to find the lost unity of nature and spirit, form and life.